2021
DOI: 10.1097/ijg.0000000000001742
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Glaucoma in Rural Kenya: Results From a Teleglaucoma Pilot Project in Nyamira, Kenya

Abstract: Precis: A teleglaucoma (TG) case-finding model was used in Kenya. Of the patients, 3.46% had definite glaucoma and 4.12% were glaucoma suspects. Most cases were of moderate to advanced stage and referred for further assessment. Purpose: The aim was to evaluate glaucoma prevalence in a high-risk population using a TG model. Methods: Patients aged 35 or over were referred to the TG program from the outpatient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…16 Another study demonstrated the benefit of a similar teleglaucoma model in detecting glaucoma, with a prevalence of 3.46% in a high-risk population in Kenya. 17 With the increasing burden of glaucoma in the coming years, the ability to detect disease at an earlier stage will become even more important, especially in communities where people are disproportionately affected, as in some countries in Africa.…”
Section: Teleglaucomamentioning
confidence: 99%
“…16 Another study demonstrated the benefit of a similar teleglaucoma model in detecting glaucoma, with a prevalence of 3.46% in a high-risk population in Kenya. 17 With the increasing burden of glaucoma in the coming years, the ability to detect disease at an earlier stage will become even more important, especially in communities where people are disproportionately affected, as in some countries in Africa.…”
Section: Teleglaucomamentioning
confidence: 99%